Prophylactic oophorectomy is recommended in female patients with pseudomyxoma peritonei of an appendiceal origin - Fu, Fengxian; Ma, Xulan; Weng, Zhen; Lu, Yiyan; Xu, Hongbin; Ma, Ruiqing (Frontiers in Oncology, 2025)
ObjectiveTo analyze the clinical efficacy of hysterectomy and bilateral salpingo-oophorectomy (BSO) in female patients with pseudomyxoma peritonei (PMP) of an appendiceal origin as well as to identify the prognostic factors associated with overall survival (OS) to reduce adverse physical or psychological effects on women.MethodsA retrospective analysis was conducted to evaluate the prognostic factors in female patients with PMP of an appendiceal origin who underwent cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) including BSO at our hospital between January 2011 and December 2020. Patients were also divided into high and low grade group according to pathology subtype. The data were analyzed by using Chi-square, univariate and multivariate cox regression methods, and survival was evaluated by Kaplan-Meier method.ResultsWe included 178 patients with PMP of an appendiceal origin who underwent BSO, and 134 (75.3%) had histopathological confirmed ovarian metastases. In the low-grade group, ovarian involvement and completeness of cytoreduction (CCR) acted as independent predictors of poor prognosis for OS. In normal appearing uterus, ovaries, fallopian tubes, pathologic disease was still found in 15.4%, 7.8%, and 22.8% respectively. In abnormal appearing uterus, ovaries, fallopian tubes, pathologic disease was found in 95.5%, 96.6%, and 94.2% respectively. Moreover, multivariate analysis revealed that a high-grade histopathological subtype of PMP and CCR 2/3 were independent predictors of OS.ConclusionBased on these data, strong consideration should be given to removal of gynecologic organs in cases of appendiceal peritoneal disease even when normal in appearance, after taking into account each individual patient’s fertility concerns.